EMOTIONAL MANAGEMENT AND EDUCATIONAL QUALITY - Mera Rodas, Anibal (2021)
The subject of this study arises from the requirement to demonstrate the influence of the management of emotions to improve educational quality in the educational context from the perceptions of the directors of a Private Educational Institution in the province of Chiclayo. For this reason, it was proposed as an objective to analyze the influence of the management of emotions in the improvement of the educational quality of a Non-State Educational Institution. The present research has a qualitative approach, it was mainly aimed at exploring and obtaining an understanding of opinions, beliefs, motivations, etc. of managers regarding the management and direction of emotions to achieve educational quality. The single case study analysis was used and the semi-structured interview, as it was the most indicated to fulfill this research purpose. The analysis of the findings allowed us to discover that the directors have as their main priority the training of parents through scholar activities and programs, it was also possible to verify that the educational community carries out its activities for transcendent reasons; the trust of the directors in their teachers is reflected in the coordinated work with their peers and students; likewise, they seek to spread the ideology of the school among the agents of education through a leadership based on values. It is concluded that the management of emotions constitutes a determining factor for the achievement of educational quality. Keywords: Performance; teacher; Educational training; pedagogical innovation; Lidership.